Quantitative high-throughput measurement of bulk mechanical properties using commonly available equipment. Issue 1 (28th October 2022) - Griffith, Justin E.; Chen, Yusu; Liu, Qingsong; Wang, Qifeng; Richards, Jeffrey J.; Tullman-Ercek, Danielle; Shull, Kenneth R.; Wang, Muzhou
Abstract : A quantitative, high-throughput, and colorimetric method is reported for characterizing the fracture stresses of bulk soft materials using common equipment. Throughput is on the order of 10 3 samples per run, with comparable accuracy to a rheometer. Abstract : Machine learning approaches have introduced an urgent need for large datasets of materials properties. However, for mechanical properties, current high-throughput measurement methods typically require complex robotic instrumentation, with enormous capital costs that are inaccessible to most experimentalists. A quantitative high-throughput method using only common lab equipment and consumables with simple fabrication steps is long desired. Here, we present such a technique that can measure bulk mechanical properties in soft materials with a common laboratory centrifuge, multiwell plates, and microparticles. By applying a homogeneous force on the particles embedded inside samples in the multiwell plate using centrifugation, we show that our technique measures the fracture stress of gels with similar accuracy to a rheometer. However, our method has a throughput on the order of 10 3 samples per run and is generalizable to virtually all soft material systems. We hope that our method can expedite materials discovery and potentially inspire the future development of additional high-throughput characterization methods.